Examination of the prevalence of conduct disorder among young Offenders: A case study of Shikusa Borstal Institution, Kenya - Moracha, Edward Ngubo; Mbiriri, Michael; Bironga, Sophia (Research Journal in Advanced Social Sciences, 2021)
Conduct disorder among juvenile offenders is a very critical phenomenon not only in Kenya but also globally. The global prevalence of conduct disorder among children and adolescents is estimated to range from 2 - 10%, indicating the biggest health and social challenge that nations of the world have to confront. The study aimed to examine the prevalence of conduct disorder and its influence among young offenders in Shikusa Borstal Institution. The study employed Psychoanalytic Theory by Sigmund Freud and Social Learning Theory by Albert Bandura. The study adopted a descriptive research design. The target population was 250, simple random and census sampling methods were applied to select 101 respondents as the sample size. Primary data was gathered through closed-ended questionnaires, interview schedule and focus group discussions. Descriptive and inferential statistical techniques were utilized to analyze quantitative data while verbatim accounts were used for qualitative data. The results were presented using tables and figures. The study concluded that the prevalence of conduct disorder had a negative and significant relationship with conduct disorder. The study recommended that policy makes should come up with policies that would improve positive thinking among young people. This would reduce negative attitude of young people that leads to law breaking.